2022
DOI: 10.1093/cid/ciac086
|View full text |Cite
|
Sign up to set email alerts
|

Current Antiretroviral Treatment Among People With Human Immunodeficiency Virus in the United States: Findings from the Centers for AIDS Research Network of Integrated Clinic Systems Cohort

Abstract: Among 14,049 people with HIV in care in 2019-2020, 96% were treated with antiretroviral therapy (ART). Current antiretroviral treatment patterns highlight high uptake of guideline-recommended ART regimens including second-generation integrase strand transfer inhibitors (dolutegravir, bictegravir) and tenofovir alafenamide, especially in ARV-naïve individuals initiating ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The time period of this study (2011-2021) is representative of the era with updated recommendations for HIV treatment, including immediate initiation of ART following HIV diagnosis [22]. Furthermore, within CNICS, almost all PWH are prescribed ART (>96% in 2019-2020) [62]. Therefore, we suspect this HR may indicate PWH not taking ART having more recently diagnosed HIV, and less time living with HIV to impact the development of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The time period of this study (2011-2021) is representative of the era with updated recommendations for HIV treatment, including immediate initiation of ART following HIV diagnosis [22]. Furthermore, within CNICS, almost all PWH are prescribed ART (>96% in 2019-2020) [62]. Therefore, we suspect this HR may indicate PWH not taking ART having more recently diagnosed HIV, and less time living with HIV to impact the development of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study recently presented at CROI demonstrated the changes in ART among PWH in the United States over time. 26 It showed the very rapid transition from tenofovir disoproxil fumarate to tenofovir alafenamide fumarate over the past 3 years. Figure 4 demonstrates the rapid change in single-tablet regimens.…”
Section: Lesson 3: Timely Datamentioning
confidence: 99%